Alterations in the Levels of Growth Factors in Adolescents with Major Depressive Disorder: A Longitudinal Study during the Treatment with Fluoxetine - Becerril-Villanueva, Enrique; Pérez-Sánchez, Gilberto; Alvarez-Herrera, Samantha; Girón-Pérez, Manuel Iván; Arreola, Rodrigo; Cruz-Fuentes, Carlos; Palacios, Lino; de la Peña, Francisco R.; Pavón, Lenin (Mediators of Inflammation, 2019)
Major depressive disorder (MDD) has a prevalence of 5% in adolescents. Several studies have described the association between the inflammatory response and MDD, but little is known about the relationship between MDD and growth factors, such as IL-7, IL-9, IL-17A, VEGF, basic FGF, G-CSF, and GM-CSF. It must be appointed that there are scarce reports on growth factors in adolescents with MDD and even fewer with a clinical follow-up. In this work, we evaluated the levels of growth factors (IL-7, IL-9, IL-17A, VEGF, basic FGF, G-CSF, and GM-CSF) in MDD adolescents and the clinical follow-up during eight weeks of treatment with fluoxetine. Methods. All patients were diagnosed according to the DSM-IV-TR, and the severity of the symptoms was evaluated using the Hamilton Depression Rating Scale (HDRS). Growth factors IL-7, IL-9, IL-17A, VEGF, basic FGF, G-CSF, and GM-CSF were quantified by cytometric bead array using serum samples from 22 adolescents with MDD and 18 healthy volunteers. Results. All patients showed clinical improvement since the fourth week of pharmacological treatment according to the HDRS. Considerably higher levels of IL-7, IL-9, IL-17A, VEGF, basic FGF, G-CSF, and GM-CSF were detected in MDD adolescents as compared to healthy volunteers. A significant but temporal decrease was detected in basic FGF, G-CSF, and GM-CSF at week four of fluoxetine administration. Conclusions. To the best of our knowledge, this is the first report to show alterations in the levels of growth factors, such as IL-7, IL-9, IL-17A, VEGF, basic FGF, G-CSF, and GM-CSF in MDD adolescents during eight weeks of clinical follow-up. These disturbances might be involved in the physiopathology of MDD since such growth factors have been proven to participate in the neural development and correct functioning of the CNS; therefore, subtle alterations in it may contribute to MDD.